Sarah C. Murray, The Collapse of the Mycenaean Economy. Imports, Trade and Institutions 1300–700 BCE. - Dickinson, Oliver (Journal of Greek Archaeology, 2021)
This book derives from a PhD dissertation defended at Stanford University in 2013, added to by further research in following years. It treats a topic of considerable importance in any discussion of the degree of continuity between the civilisations of the Aegean Bronze Age and that of the early Greeks, which was becoming well established in the eighth century BC (all dates cited subsequently are BC), and the reality or otherwise of an intervening ‘dark age’.